Fecal microbiota and metabolites are distinct in a pilot study of pediatric Crohn's disease patients with higher levels of perceived stress. (January 2020) - Mackner, Laura M.; Hatzakis, Emmanuel; Allen, Jacob M.; Davies, Ronald H.; Kim, Sandra C.; Maltz, Ross M.; Bailey, Michael T.
Highlights: Higher levels of perceived stress were associated with worse disease activity. Lower relative abundances of bacteria in phylum Firmicutes in higher stress group. Genus Anaerostipes was lower and Parabacteroides was higher in the high stress group. Differences were independent of medications, disease severity, disease duration, diet. Levels of the metabolite alanine were higher in youth with higher stress. Abstract: Stress is associated with increased Crohn's Disease (CD) activity. This pilot study tested whether pediatric patients with CD reporting higher levels of perceived stress exhibited differences in the fecal microbiome and metabolome. The perceived stress scale (PSS) questionnaire was administered within 2 days of collecting a stool sample for microbiome (using 16S rRNA gene sequencing) and metabolome (using NMR metabolomics) analyses. Higher levels of perceived stress were correlated with increased disease activity on the short Pediatric Crohn's Disease Activity Index (sPCDAI). Patients with High PSS scores vs. Low PSS scores based on a median split had significantly lower relative abundances of Firmicutes and Anaerostipes, as well as higher relative abundances of Parabacteroides . Fecal alanine and nicotinate were also significantly different in patients with High vs. Low PSS Scores. This pilot study suggests that the fecal microbiome and metabolome differs in pediatric patients with CD and high perceived stress.